Financial Integration, Euro and the Twin Deficits of Southern Eurozone Countries - Kosteletou, Nikolina E. (Panoeconomicus, 2013)
The purpose of this study is the examination of the relationship between fiscal and Current Account balances for the countries of southern eurozone. The twin deficit hypothesis is tested within the context of a portfolio model involving variables from the financial sector. Empirical analysis is conducted with panel data, for the period 1991-2011. Evidence is provided to support the twin deficit hypothesis. Additionally, it is found that it is not only the fiscal policy of the southern eurozone countries that affects their Current Account balances, but also the fiscal policy of the eurozone surplus countries of the north. Interdependence of eurozone countries suggests that fiscal policy can be used for the elimination of external disequilibrium. Therefore, fiscal policy should be coordinated but not uniformly applied. Key words: Current Account, Budget balance, Twin deficits, Financial integration, Fiscal coordination. JEL: F32, F36, F41.